Marketing Strategy and Capacity Planning for Pastel Chic - Utami, Sarah Sari; Aldianto, Leo (The Indonesian Journal of Business Administration, 2014)
Abstractâ€”Nowadays, there are so many brands of Muslim fashion competing to enter the same market. Pastel Chic as a new brand of Muslim fashion strives to attract customer with a different product. But after running 4 months, there is no significant improvement in term of sales. Tight competition, high production cost, and lack of awareness in social media are problems faced by Pastel Chic thus resulting in unachieved sales target. The finding in this research show that there are three root causes which cause unachieved sales target that are unplanned capacity production, marketing communication is not maximal, and design characteristic design of product is not strong. Root causes analysis in this research are determined based on conceptual framework that contains of competitor analysis, capacity planning and integrated marketing communication. The results this research generate a marketing strategy and capacity planning strategy that can be implemented by Pastel Chic to achieve its objective that is increase of brand awareness and increase of sales and profit. By doing capacity planning, marketing communication and media mix, also product planning and development, it is expected that brand awareness of Pastel Chic will increase and sales target can be achieved. The implementation of business solution will be implemented for 1 year and will be evaluated every 3 months.Â Keywords: Integrated Marketing Communication, product planning and development, Muslim fashion product.